A compact ultra wide band bandpass filter with dual band notch designed based on composite right/left‐handed transmission line unit cell. Issue 9 (23rd October 2018) - Janapala, Doondi Kumar; Nesasudha, M.
Abstract: In this article, we propose an ultra wide band (UWB) bandpass filter with dual notch characteristics. The proposed filter is designed based on composite right/left handed (CRLH) transmission lines. The filter is having a compact size of 2.4 mm × 8.78 mm and printed on FR4 material with relative permittivity 4.4 with thickness 1.6 mm. The filter is constructed by series of strip lines, which forms interdigital capacitance and shunt inductors allowing both low and high frequencies of the UWB to pass. The selectivity in lower and higher parts of the UWB is achieved by the slots etched from the ground plane. The dual band notch is obtained at 4 GHz and 7 GHz using the L‐shaped strip lines on both sides of the filter. The comparative analysis of the proposed UWB band pass filter without and with notch characteristics is presented with the help of the S11 and S21 curves.